PrEP: controversy, agency and ownership - Cairns, Gus P (J Int AIDS Soc, 2016)
Pre-exposure prophylaxis (PrEP) has been and continues to be an intervention that causes controversy and debate between stakeholders involved in providing or advocating for it, and within communities in need of it. These controversies extend beyond the intrinsically complex issues of making it available. In this commentary, some of the possible roots of the air of dissent and drama that accompanies PrEP are explored. The similarities between the controversies that dogged the earliest human trials of PrEP and the ones we see today in the era of licensing and implementation are explored. We outline five mediating principles or cultural norms that may influence arguments about PrEP differently. Three areas of specific concern are identified: medical risk versus benefit, distrust and fear of healthcare interventions, and fears for individual responsibility and community cohesion. The fear that PrEP may somehow represent a loss of control over one or more of these domains is suggested as an underlying factor. The development of countervailing measures, to institute greater community “ownership” of PrEP, and concomitant improvements in the sense of individual agency over sexual risk are outlined and recommended.